A Corpus-Based Analysis of ‘Muslim’ in the LCC Indonesia 2023 - Prihantoro, Prihantoro; Maghfiroh, Adinda; Hidayah, Siti Rahmawati; Nuradita, Rizki Dwi; Dharmawan, Ronald (Proceedings International Conference of Culture and Sustainable Development; Vol 3 (2025): PROCEEDINGS ICOCAS, 2025)
Some scholars have visited the representation of Muslims in various English corpora. Unlike previous studies, we here focus on how ‘muslim’ is represented in LCC 2023, an Indonesian Corpus in CQPweb Lancaster. We aim to (1) identify strong collocates of ‘muslim’, (2) profile the diachronic distribution of collocates over years (3) semantically categorize them based on Baker et al.’s (2013) classification. Collocates were obtained using Dice’s Coefficient and ranked from high to low. As many as 50 of the strongest noun collocates per year. We exported the collocates to identify recurring collocate patterns. Semantic annotations were performed to categorise each collocate. We discover both positive and negative sentiment collocates used to represent ‘muslim’ in the corpus. This shows how ‘muslim’ is portrayed in the corpus with both positive and negative images.
Keywords: Collocation, Collocates, Muslim, Corpus Linguistics, Semantic Categorization